An Evaluation of Genetic Algorithm Solutions in Optimization and Machine Learning - Carrick, Christina; Macleod, Kevin (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
A genetic algorithm (GA) is a search algorithm in which a solution is evolved through natural selection. A new set (population) of solutions is created from a random partial exchange of information between the best solutions of the previous generation. This results in increasingly better solutions in successive generations. Traditional search methods have either been